Effect of combined use of mustard oilcake, ammonium sulphate, and superphosphate on fish and aquatic ecosystem - Sarkar, S K (Indian Journal of Fisheries, 2011)
There are a few investigations in India on the influence of different chemical fertilizers and organic manures on commercially important fish and aquatic ecosystem. The use of fertilizers in fish ponds is on increase. However, their liberal application causes drastic decline in the abundance offish and their food organisms due to toxic action of nitrogen fertilizers and their metabolites